The relationship between the bunkie-test and selected biomotor abilities in elite-level rugby players - Van Pletzen, Danel (Stellenbosch : University of Stellenbosch, 2010)
Thesis (M Sport Sc (Sport Science)--University of Stellenbosch, 2010.